Life Balance and Work Addiction Among African Americans. Issue 1 (7th March 2018) - Balkin, Richard S.; Reiner, Summer M.; Hendricks, LaVelle; Washington, Ahmad; McNeary, Sian; Juhnke, Gerald A.; Hunter, Quentin
Abstract : A dearth of counseling literature examines the experiences of people of color, including African American women and men, in relation to work–life balance. The authors, therefore, investigated the association between life‐balance domains and work addiction for African Americans. A multiple regression analysis of 115 African American participants (47 men, 68 women) indicated a significant relationship between life‐balance domains and work addiction. In particular, community support was an important indicator of decreased work addiction. Career counselors and mental health counselors need to develop an understanding of how extended familial and social networks assist African American clients in effectively managing work–life balance.